Social Determinants of Health and Polygenic Susceptibility in Nonsyndromic Ascending Aortic Aneurysm - Navraj S. Sagoo; Rajveer Sagoo; Jaden F. LeGate; Isabela A. Maluli; Charlene N. Radler; Tianci Wang; Mohanakrishnan Sathyamoorthy (Journal of the American Heart Association, 2026)
Background Nonsyndromic ascending aortic aneurysm (AsAA) may remain clinically silent until dissection or rupture. The contributions of multidomain social determinants of health (SDOH) and polygenic susceptibility to AsAA risk are not well defined. Methods In a cross‐sectional analysis of 124 180 participants in the National Institutes of Health All of Us Research Program, 14 SDOH measures were summarized as a standardized composite score, and an ascending aortic diameter polygenic risk score (PRS; polygenic score, 004927) was standardized within ancestry strata. Associations were tested using Firth‐penalized logistic regression adjusted for clinical risk factors; discrimination was assessed by area under the receiver operating characteristic curve. Results Among 124 180 participants, 346 had AsAA. Compared with controls, cases were older (mean age, 70.7±9.0 versus 57.1±16.4 years) and more often men (60.4% versus 37.1%). Each 1‐SD increase in the SDOH composite was associated with AsAA after clinical adjustment (odds ratio, 1.21 [95% CI, 1.04–1.40]) and in joint models including PRS (odds ratio, 1.28 [95% CI, 1.11–1.48]). The PRS was associated with AsAA after clinical adjustment (odds ratio per SD, 1.94 [95% CI, 1.74–2.16]); AsAA prevalence increased from 0.08% (lowest PRS decile) to 0.77% (highest). SDOH and PRS were minimally correlated ( r =−0.002), with no evidence of interaction (interaction odds ratio, 1.03; P =0.62). Discrimination improved from basic covariates (area under the receiver operating characteristic curve, 0.774) to clinical covariates (area under the receiver operating characteristic curve, 0.841) and to the full model including SDOH and PRS (area under the receiver operating characteristic curve, 0.870 [95% CI, 0.851–0.889]). Conclusions Social adversity and higher polygenic susceptibility were associated with nonsyndromic AsAA, supporting further study of integrated social and genetic risk stratification.